Rekonstruksi Nilai Filosofis dalam Ekonomi Islam Menuju Kesejahteraan Universal - Didi Handono Syahputra; Muhammad Aldi Pratama; Ahmad Wahyudi Zein; Muhammad Rizky Putra (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Islamic economics was born as a response to the need for an economic system that is not only oriented towards profit, but also towards social justice and human welfare. This article discusses the reconstruction of philosophical values ​​in Islamic economics as an effort to create an inclusive and sustainable economic order. With a conceptual approach, this study highlights principles such as justice, balance, and social responsibility that are at the core of Islamic economics. These values ​​are reinterpreted in a modern context to address global challenges, including economic disparities and moral crises in the business world. The results of the analysis show that the application of the philosophical values ​​of Islamic economics is not only able to improve the economic structure, but also create universal welfare that is in line with the objectives of sharia (Maqashid Syariah). Therefore, the integration of these values ​​is important in formulating fair and ethical economic policies.